Belize : Selected Issues. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper on Belize reviews the external competitiveness, balance sheet currency mismatch, and public sector debt. Belize is a small, open economy and highly dependent on external trade. Real wages in the private sector have increased only slightly. Belize's exports of commodities grew strongly in volume terms during the last 10 years. The currency mismatch and liquidity pressures point to a growing exchange rate risk. Belize would have to maintain a significant primary fiscal surplus to reduce indebtedness over the medium term.